2020
DOI: 10.1073/pnas.1910668117
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric sheet actuators with programmable bioinstructivity

Abstract: Stem cells are capable of sensing and processing environmental inputs, converting this information to output a specific cell lineage through signaling cascades. Despite the combinatorial nature of mechanical, thermal, and biochemical signals, these stimuli have typically been decoupled and applied independently, requiring continuous regulation by controlling units. We employ a programmable polymer actuator sheet to autonomously synchronize thermal and mechanical signals applied to mesenchymal stem cells (MSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…This study suggested that mechanically activated Ca 2+ influx through Piezo1 is required for YAP nuclear localization when cells grow on a stiff surface. The response of YAP localization to Ca 2+ influx under this cellular mechanical circumstance appears to be opposite to those described above when cells are compressed (He et al, 2018;Deng et al, 2020). Notably, the mechanical force comes from the FIGURE 1 | A proposed model for the role of CaAR in the Hippo pathway activation.…”
Section: Ca 2+ Signaling Inhibits the Hippo Pathwaymentioning
confidence: 89%
“…This study suggested that mechanically activated Ca 2+ influx through Piezo1 is required for YAP nuclear localization when cells grow on a stiff surface. The response of YAP localization to Ca 2+ influx under this cellular mechanical circumstance appears to be opposite to those described above when cells are compressed (He et al, 2018;Deng et al, 2020). Notably, the mechanical force comes from the FIGURE 1 | A proposed model for the role of CaAR in the Hippo pathway activation.…”
Section: Ca 2+ Signaling Inhibits the Hippo Pathwaymentioning
confidence: 89%
“…Owing to the changes in intercellular distance and substrate stiffness, the properties of cell‐like proliferation, differentiation may get affected. [ 110 ] Apart from the holistic heating of these SMPs, the indirect heating at the specialized location the material through focused infrared or ultrasound stream can be used. [ 111,112 ] The reinforcement of nanomaterials like carbon nanotubes/graphene may not only improve them for their spatial mechanical properties but also serve as electrodes to stimulate the implanted tissue to elicit appropriate cellular response and sense the cellular microenvironment through electrical and magnetic fields.…”
Section: Smart Biomaterialsmentioning
confidence: 99%
“…cPCLBA containing crystallizable poly(εcaprolactone) and amorphous poly(n-butylacrylate) segments was synthesized, programmed, and punched into circular sheets with a diameter of 10 mm fitting 24-well cell culture plates according to the methods described in our previous report. [11] Each well of the 24-well plates was filled with 0.8 mL Stem-MACS™ MSC Expansion Medium (Miltenyi Biotec, Bergisch Gladbach, Germany) to immerse the cell-laden polymer sheet and supplied with 5 vol% CO 2 for cell maintenance. The periodic thermal fluctuation between 37 and 10°C was realized by computer-controlled thermochambers (Instec, Colordao, USA).…”
Section: Preparation Of Shape-memory Polymer Actuator Sheets and Generation Of Periodic Thermomechanical Stimulimentioning
confidence: 99%
“…[10] Cellular behaviors and functions of MSCs can be altered by the biochemical and biophysical signals as well as thermal and mechanical cues. [11] Priming TLR4 on MSC surfaces with chemical compounds results in pro-inflammatory and antigen-presenting cell-like phenotypes leading to release of pro-inflammatory cytokines and recruitment of immune cells to raise the immune reactions. However, priming of TLR3 makes the switching of MSCs toward an anti-inflammatory phenotype to suppress immune response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation